К ВОПРОСУ О НЕДОПУСТИМОСТИ В КАЧЕСТВЕ ДОКАЗАТЕЛЬСТВ ФАКТИЧЕСКИХ ДАННЫХ, ПОЛУЧЕННЫХ С ПРИМЕНЕНИЕМ В ХОДЕ ДОКАЗЫВАНИЯ МЕТОДОВ, ПРОТИВОРЕЧАЩИХ СОВРЕМЕННЫМ НАУЧНЫМ ЗНАНИЯМ - Isenov, E.E. (Journal of actual problems of jurisprudence, 2019)
In article the bases of impossibility of admissibility of the facts as proofs which provided in article 116 of Procedural criminal law of RK are considered.